Self-Biased-SMA Drive PU Microgripper with Force Sensing in Visual Servo. (28th June 2013) - Chang, Ren-Jung; Shiu, Chih-Cheng; Cheng, Chih-Yi
An innovative design of a polyurethane microgripper system with force sensor is developed for the measurement of gripping force in vision-based control. A microgripper mechanism integrated with a force sensing arm is fabricated by an excimer laser. The microgripper is actuated by a self-biased-SMA (Shape Memory Alloy) actuator. A computer-vision method through the ERES (Extended Regional Edge Statistics) algorithm is employed to track the motion of gripper. The position information of the gripping point together with the deflection of the force sensing arm is utilized for sensing force. A fuzzy expert with a PI controller in a visual servo is employed to test the performance of sensing the gripping force in grasping of 38μm diameter metal rod. In the performance test, the microgripper system provides a maximum gripping size of 40μm, a maximum force resolution of 1μN and a maximum gripping force of 58μN.